Directors' reliance and responsibility to supervise and auditors' duty of care: Planassurance PAC formerly known as Patrick Lee Pac V Gaelic Inns Pte Ltd - Mohd. Sulaiman, Aiman @ Nariman (LexisNexis, 2009)
The duty of care, skill and diligence requires directors to be involved in managing the company, so much so that being a passive director is itself a breach of duty. n1 In reality, directors do not manage all of the company's business themselves but leave appointed employees to deal with specific scope of work. However, this does not resolve the problem faced by directors in delegating authority. The extent to which directors may rely on delegates in the exercise of power or on the information provided by others to enable directors to make business decisions is often fact-sensitive.